Neighbourhoods and city quarters in antiquity design and experience - Haug, Annette 1977-; Hielscher, Adrian 19XX-; Krüger, Anna-Lena; Walter de Gruyter GmbH & Co. KG (Berlin/Boston De Gruyter, 2023)
This volume focuses on the socio-spatial organisation of ancient cities, and more specifically on Late Republican and Imperial Italy. Referring to a praxeological and phenomenological perspective, it looks at neighbourhoods and city quarters as basic categories of design and experience
English
Keywords: Classical Greek & Roman archaeology; Archaeology by period / region; Ancient World; Urban studies; social topography; antiquity decor; Konferenzschrift -- 2021 -- Kiel; Online